Effectiveness of treadmill assisted gait training in stroke survivors: A systematic review and meta-analysis - Asmare Yitayeh Gelaw (Global Epidemiology, 2019)
Background: Restoring one's walking ability and balance is a major goal of gait rehabilitation in stroke survivors. The demands of the treadmill and over ground walking training are different in its impact on gait parameters, and treadmill training with or without body weight support may offer a favorable effect on gait parameters. Objective: The objective of this review was to summarize the current best evidence for the effectiveness of treadmill training in improving walking speed, walking distance, and balance of stroke survivors. Methods: A comprehensive search of literature published between 2000 and April 2019 was conducted using the following six electronic databases; CINAHL, MEDLINE, AMED, EMBASE, PUBMED, and PEDro. Only randomized controlled trials evaluating the effect of treadmill training on walking balance, speed and distance post-stroke were included. Physiotherapy Evidence Database (PEDro) was used to assess the risk of bias of included trials. Qualitative synthesis of evidences was prepared and meta-analysis was implemented to draw pooled effects of treadmill training on the selected walking parameters. Results: Eight trials involving 695 participants met the inclusion criteria. Meta-analysis showed no statistically significant difference between treadmill and over ground walking groups for walking speed and balance. However, treadmill training improved walking distance during immediate post-intervention period (MD 13.03 m, 95% CI 1.21, 24.85, I2 = 0%) but the effects were lost during follow up periods (MD 10.6 m, 95% CI −4.0, 25.3, I2 = 0%). Conclusion: Treadmill training following stroke offers improvement in walking distance. However, it has no significant advantage in improving walking speed and balance over over-ground walking training. A large systematic review and meta-analysis of randomized controlled trials could provide more definitive evidence.